2017
DOI: 10.20867/thm.23.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Adoption of Mapping Apps: A Utaut2 Perspective of Smart Travellers

Abstract: Purpose -Mapping apps are location based travel apps used for navigation and routing. These apps are gaining worldwide popularity because of its enormous potential. Despite of the growing popularity and utility of the mapping apps, the published literature in this area is scarce, leaving an unexplored area of research. Thus, the current study aims to identify factors affecting tourist's intentions to use mapping apps while travelling. Design -The Extended Unified theory of acceptance and use of technology (UTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
1
28

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 50 publications
(41 reference statements)
15
71
1
28
Order By: Relevance
“…Based on the calculating result of hypothesis test (H5), H5 is accepted. This result is in line with previous studies by Venkatesh, et al, [28] and Gupta, A., & Dogra, N. [36] which state hedonic motivations were found to be statistically significant in explaining behavioural intentions. This implies that to find pleasure and joy could be the users' intention to use digital banking.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the calculating result of hypothesis test (H5), H5 is accepted. This result is in line with previous studies by Venkatesh, et al, [28] and Gupta, A., & Dogra, N. [36] which state hedonic motivations were found to be statistically significant in explaining behavioural intentions. This implies that to find pleasure and joy could be the users' intention to use digital banking.…”
Section: Resultssupporting
confidence: 93%
“…Based on the calculating result of hypothesis test (H3), H3 is rejected. This result is corresponding with the previous research that stated insignificant relationship between social influence and behavioural intentions [34], [35] also from research by Gupta and Dogra [36] the results revealed no significant relationship of social influence on behavioural intentions. This can be caused by their environment and influence of other people has not become their initial reason to use digital banking.…”
Section: Resultssupporting
confidence: 91%
“…This enjoyment is a relevant predictor of the behavioral intention of the technology [38][39][40]. Other researchers with similar technologies, such as m-commerce [41] or tourist geolocation [42], show hedonic motivation as one of the main influences on the behavioral intention of these applications by users. Hence, we formed the fourth hypothesis of our research: Hypothesis 4 (H4).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 91%
“…(2018) bahwa terdapat hubungan yang positif dan signifikan antara niat perilaku dangan perilaku terhadap produk uang elektronik e-money. Hal yang sama juga di temukan pada penelitian Grupta & Dogra (2017) bahwa keputusan individu untuk melakukan suatu perilaku ditentukan oleh niat untuk melakukan. Niat berperan penting dalam menentukan tindakan manusia.…”
Section: Tabel 1 Goodness Of Fit Structural Equation Model (Sem)unclassified